Students' cyberslacking behaviour in e-learning environments: the role of the Big Five personality traits and situational factors - Koay, K.Y. (Emerald Group Holdings Ltd., 2022)
Purpose: Online learning has become more popular than ever in higher education owing to the COVID-19 pandemic. However, this has also intensified students' propensity to engage in cyberslacking behaviour during online classes without the physical presence of instructors to monitor their behaviour. Hence, this research aims to investigate the association of the Big Five personality traits and situational factors with students' cyberslacking behaviour during online classes. Design/methodology/approach: A self-administered survey questionnaire was distributed to current university students undertaking online modules this semester. In all, 194 completed surveys were obtained for further analysis. Findings: The results reveal that extraversion, conscientiousness, neuroticism and apathy towards course material have a significant association with at least one of the cyberslacking dimensions (sharing, shopping, real-time updating, accessing online content and gaming/gambling). However, agreeableness, intellect/imagination and class engagement are found to have no significant association with all the dimensions of students' cyberslacking behaviour during online classes. Originality/value: This study fills the research gaps by empirically testing the association of the Big Five personality traits and situational factors with students' cyberslacking behaviour in e-learning environments. Several limitations and future research are also discussed. Â© 2022, Emerald Publishing Limited.